Adsorption of SF6 Decomposed Species on Ti3C2O2 and Ti3C2F2 with Point Defects by DFT Study. Issue 7 (4th June 2021) - Kong, Lingyan; Liang, Xiongyi; Deng, Xiangxuan; Guo, Chen; Wu, Chi‐Man Lawrence
Abstract: The high specific surface area and electrical conductivity of new 2D metal carbide MXenes make them become a suitable candidate as sensor platform of the gas sensor. Herein, density functional theory (DFT) is implemented to investigate the adsorption of the SF6 decomposed gases (SOF2, SO2, and H2 S) on Ti3 C2 O2, Ti3 C2 F2, and Ti3 C2 (OH)2 . Modification of the surface of Ti3 C2 O2 and Ti3 C2 F2 by O and F point vacancy, respectively, is then performed to improve the adsorption performance. The band structure, charge density differences, electron localization function (ELF), and projected density of states (PDOS) are investigated to study the adsorption mechanism. The results indicate that as compared with the weak adsorption on pristine Ti3 C2 O2 and Ti3 C2 F2, the SOF2, SO2, and H2 S gas molecules tend to be chemisorbed on Ti3 C2 O2 and Ti3 C2 F2 with point vacancy with high adsorption energies. Furthermore, the study of electronic properties suggests that all adsorption systems show high electronic conductivity and the exposed Ti atoms by point defect mainly contribute to the formation of ionic bond with high adsorption energy. Thus, the present results show that Ti3 C2 O2 and Ti3 C2 F2 with point vacancy are feasible novel sensing materials to detect SF6 decomposed species with high sensitivity and low electronic noise. The sensitive detection capability of SO2 is particularly noticeable. Abstract : Using density functional theory and Car–Parrinello molecular dynamics method, Ti3 C2 O2 and Ti3 C2 F2 with point vacancy are found to be feasible novel sensing materials to detect SF6 decomposed species (SO2, H2 S, and SOF2 ) in Gas‐insulated switchgear with high sensitivity and low electronic noise. The sensitive detection capability of SO2 is particularly effective.